Immune Functional Assays, From Custom to Standardized Tests for Precision Medicine - Albert-Vega, Chloé; Tawfik, Dina M.; Trouillet-Assant, Sophie; Vachot, Laurence; Mallet, François; Textoris, Julien (Frontiers in Immunology, 2018)
The immune response is a dynamic system that maintain the integrity of the body, and more specifically fight against infections. However, an unbalanced host immune response is highlighted in many diseases. Exacerbated responses lead to autoimmune and allergic diseases, whereas low or inefficient responses favour opportunistic infections and viral reactivations. Conflicting situations may also occur, such as in sepsis where inflammation and compensatory immunosuppression make it difficult to deploy the appropriate drug treatment. Till the current day, assessing the immune profile of patients remains a challenge. This is especially due to the inter-individual variability – a key feature of the immune system – which hinders precise diagnosis, prognosis and therapeutic stratification. Our incapacity to practically interpret the host response may contribute to a high morbidity and mortality, such as the annual 6 million worldwide deaths in sepsis alone. Therefore, there is a high and increasing demand to assess patient immune function in routine clinical practice, currently met by Immune Functional Assays (IFAs). Immune monitoring tools hold a plethora of potentials that include the precise diagnosis of infections, as well as prediction of secondary and latent infections. Current available products are devoted to indirect pathogen detection such as Mycobacteria tuberculosis which quantifies interferon gamma release (IGRA), after pathogen-specific stimulation of T-cells. In addition, identifying the status and the underlying factors of immune dysfunction e.g. in septic patients may allow achieving immune recovery. Tools to monitor and stratify the immune status are currently being studied but they still have many limitations such as technical standardization, biomarkers relevance, systematic interpretation and need to be simplified, in order to set the boundaries of “healthy”, “ill” and “critically ill” responses. Thus, the design of new tools that give a comprehensive insight of the immune functionality, at the bedside and in a timely manner represent a leap towards immunoprofiling of patients.